Multifactor-coupled study on freeze-thaw forces of rocks in cold regions - Zhao, Yonghui; Hu, Kun; Han, Deming; Lang, Yongxian; Zhang, Lin (Frontiers in Earth Science, 2024)
This study delves into the mechanical properties of steep and rocky slopes subjected to long-term freeze-thaw actions. Considering the unique climatic conditions in cold regions, especially the significant impact of seasonal and diurnal temperature variations on slope excavation, the research focuses on a high-cold region iron ore mine. Four types of rocks commonly found in the mining area are thoroughly examined, taking into account the hydrogeological conditions of the mining area. The study systematically analyzes the mechanisms of various factors such as weathering, freeze-thaw cycles, and ice-water phase changes on the stability of cold region fractured rock masses. The research reveals that under prolonged freeze-thaw actions, crack water within the rock continuously undergoes ice-water phase changes, generating substantial freeze expansion forces that result in structural damage to the rock mass. This damage is evident not only in the development of existing microcracks but also leads to the generation of new fractures, ultimately causing deterioration in the rock mass structure. The study of the evolution patterns of freeze-thaw forces contributes to a better understanding of slope stability issues in cold region mineral resource extraction, offering crucial insights for the design, construction, and operation of related engineering projects.